THE LIFE AND CREATIVE LEGACY OF SUFI ALLAYAR - Rustamkhon Kotibov Bosithon ogli (International Scientific and Current Research Conferences, 2025)
This article explores the life and literary heritage of So‘fi Olloyor (also transliterated as Sufi Allayar), a prominent figure in the spiritual and cultural history of Central Asia. While overshadowed by more widely recognized authors such as Ahmad Yassaviy and Alisher Navoiy, Olloyor carved out his own niche as a poet, theologian, and educator. His works exhibit a profound synthesis of Sufi thought, moral instruction, and poetic creativity, extending beyond narrow religious circles and resonating with broader communities in what is today Uzbekistan. By writing in a clear and accessible style, he made complex Sufi concepts comprehensible to ordinary believers, enabling a more inclusive transmission of faith-based and ethical teachings. Through historical contextualization and literary analysis, this article highlights So‘fi Olloyor’s life story, principal themes, linguistic innovations, and spiritual-educational contributions. Reassessing his role in Uzbek culture reveals a rich tradition of vernacular Sufi poetry that blends Islamic devotion with artistic expression, and underscores the enduring impact of his moral voice on successive generations.